2011
DOI: 10.1097/aud.0b013e318201c468
|View full text |Cite
|
Sign up to set email alerts
|

Development of Auditory Processing in 6- to 11-Yr-Old Children

Abstract: Data suggest that the perception of different auditory stimuli occurs and develops using rather independent mechanisms, even for tasks that are closely related in procedure. While individual children can perform reliably on several distinct tasks, differences between individuals on the same tasks can be large. Because some of the youngest children perform reliably across time, at or near adult levels, immaturity between 6 and 11 yrs of age, as reflected in group statistics, reflects poor performance of some in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

19
97
1
7

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 112 publications
(124 citation statements)
references
References 68 publications
19
97
1
7
Order By: Relevance
“…This finding is similar to the result of another study, which showed no significant association between the two variables 23 . These findings can be explained by the fact that the test evaluates the lower brainstem, as this structure has fully matured within the first years of life, it is expected that after five years of age, all subjects are already within the normal range of function, with no response differences after this age.…”
Section: Discussionsupporting
confidence: 82%
“…This finding is similar to the result of another study, which showed no significant association between the two variables 23 . These findings can be explained by the fact that the test evaluates the lower brainstem, as this structure has fully matured within the first years of life, it is expected that after five years of age, all subjects are already within the normal range of function, with no response differences after this age.…”
Section: Discussionsupporting
confidence: 82%
“…A comparison between 8 and 11 year old children showed a general improvement in performance with age, which is consistent with suggestions that neuromaturation of some portions of the auditory system may not be complete until age twelve or later [40,41]. A similar improvement in performance with age (from 6 -10 years) was reported by Willeford for his fixed 500 Hz low-pass filtered speech test [42].…”
Section: Discussionsupporting
confidence: 73%
“…Still, a differentiation between auditory, i.e., sensory perceptual and cognitive or linguistic disorders is an important issue (Fitzgibbons and Gordon-Salant 1996; Cacace and McFarland 1998), also because APD is not always accompanied by weak phonological awareness (Sharma et al 2006). All this points to the need to clearly differentiate APD from speech disorders, which necessitates the inclusion of nonlinguistic test material (Moore 2006;Moore et al 2011). The BSA recently introduced a new consensus on a working definition: "APD is characterized by poor perception of both speech and non-speech sounds."…”
Section: Children With Auditory Processing Disordersmentioning
confidence: 99%
“…Almost all auditory skills described by the ASHA or the British Society of Audiology (BSA) can be investigated using both speech and nonspeech stimuli. Among others, there are tests investigating (1) localization or in the broadest sense spatial hearing using noise bursts (Kühnle et al 2013) or speech (Cameron et al 2006a, b), (2) discrimination of simple sounds Moore et al 2011) or speech stimuli (Kraus et al 1996), and even (3) binaural interaction based on clicks (Gopal and Pierel 1999;Delb et al 2003) or speech sounds (Willeford 1985). If auditory processing is solely measured using speech sounds, then the criteria recently established by the BSA (2011) would not be met, namely that APD is characterized by poor perception of both speech and nonspeech sounds.…”
Section: Introductionmentioning
confidence: 99%